End of an era : anecdotal stories of Flora Hill Primary School no. 4667, 1952-2007 - Pryor, Geoffrey William, 1946- (Bendigo, Vic. : G.W. Pryor, 2007)
"The history of Flora Hill Primary School, Bendigo. The school is closing in December, 2007"--Provided by publisher.
Bibliography: p. 115-116.
Keywords: Flora Hill Primary School -- History; Primary schools -- Victoria -- Bendigo -- History